(untitled) (Research, Society and Development, 2020)
The needs and expectations of consumers have been a major challenge for companies, which live in an increasingly competitive scenario. That is why launching a product that has customer acceptance is essential. This work aims to evaluate and establish relationships through the physical-chemical parameters of detergents, verifying their adjustment to the standards established by the health legislation. Five samples were collected from an industry located in the city of Campina Grande-PB, of the product and the pH and kinematic viscosity were analyzed, in triplicate, comparing the results together with the specifications provided for in Resolution No. 40/2008 of ANVISA. The results indicated that the pH and kinematic viscosity were in compliance with the resolution, indicating that the product can be purchased without harming the consumer.